2023
DOI: 10.1136/gutjnl-2023-330396
|View full text |Cite|
|
Sign up to set email alerts
|

British Society of Gastroenterology guidelines on sedation in gastrointestinal endoscopy

Reena Sidhu,
David Turnbull,
Hasan Haboubi
et al.

Abstract: Over 2.5 million gastrointestinal endoscopic procedures are carried out in the United Kingdom (UK) every year. Procedures are carried out with local anaesthetic r with sedation. Sedation is commonly used for gastrointestinal endoscopy, but the type and amount of sedation administered is influenced by the complexity and nature of the procedure and patient factors. The elective and emergency nature of endoscopy procedures and local resources also have a significant impact on the delivery of sedation. In the UK, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 215 publications
0
3
0
Order By: Relevance
“…This observed increase in anxiety, especially with symptoms that have a physical manifestation, such as wobbliness in the legs and hot or cold sweats, highlights the profound psychosomatic response that the prospect of endoscopic procedures can evoke. It is well-documented in the literature that preoperative anxiety can adversely affect not only the patient's experience of medical procedures but also their outcomes, including increased pain perception, prolonged recovery times, and, in some cases, complications during the procedure itself [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…This observed increase in anxiety, especially with symptoms that have a physical manifestation, such as wobbliness in the legs and hot or cold sweats, highlights the profound psychosomatic response that the prospect of endoscopic procedures can evoke. It is well-documented in the literature that preoperative anxiety can adversely affect not only the patient's experience of medical procedures but also their outcomes, including increased pain perception, prolonged recovery times, and, in some cases, complications during the procedure itself [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of deep sedation on the risk of colonic perforation is quite controversial[ 25 ]. In a study by Adeyemo et al [ 26 ], among a sample of 118,004 colonoscopies, it was concluded that the use of propofol was associated with an increased risk of colonic perforation.…”
Section: Colonoscopymentioning
confidence: 99%
“…In the context of drugs used for sedation in gastrointestinal endoscopy, the latest 2024 guidelines list drugs such as propofol, fentanyl, remimazolam, nitrous oxide, and pethidine as recommended drugs [ 8 ]. These guidelines do not reference the utilization of intravenous (i.v.)…”
Section: Introductionmentioning
confidence: 99%